Lingual Cyct - Fattni, Mohammad; Madan, Fakhria; Refai, Asma; Bador, Kalid; Alhojaili, Najia (Journal of Clinical Case Reports and Images, 2018)
Epidermoid cysts encountered throughout the body, only 7% occurs in the head and neck area, with the oral cavity accounting for only 1.6%. Intraoral this benign slow growing and painless entity is usually located in the submandibular, sublingual and sub mental region. They can cause symptoms of dysphagia and dyspnea and have a malignant transformation potential. Surgical excision is the treatment of choice. Described here is a case of gigantic sublingual cyst.
Keywords: Epidermoid Cyst; Sublingual Cyst; Oral Cavity; Dysphagia; Surgical Excision